Pengaruh Musikalitas Gerejawi Pemandu Lagu terhadap Pertumbuhan Iman - Ratna Katharina; Vena Melinda Tiladuru; Immanuel Christmas Banunaek; Dreitsohn Franklyn Purba (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
This study aims to analyze the influence of church musicality among song leaders at STT SAPPI on the faith growth of the congregation. Church musicality is understood as the song leaders’ technical competence, musical leadership and control, song preparation, congregational participation, and spiritual readiness. Faith growth is measured through affective, cognitive, behavioral, commitment, and life transformation dimensions. The study employs a mixed-methods approach with purposive sampling involving 11 students actively serving as song leaders. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, correlation analysis, and simple linear regression. The results indicate that the church musicality of song leaders is at a moderate level and has a positive and significant effect on faith growth (r = 0.670; R² = 0.449; p < 0.05). These findings affirm that song leaders play a strategic role in shaping worship experiences that contribute holistically to the congregation’s faith growth.